DETERMINATION OF THE ANTHRACNOSE (COLLETOTRICHUM LINDEMUTHIANUM (SACC. AND MAGN.) LAMBS. SCRIB.) RESISTANCE IN SOME TURKISH BEAN GENOTYPES BY ARTIFICIAL INOCULATION AND MOLECULAR METHODS - C. Erdinc1; O. Turkmen; S. Demir; S. Sensoy (Journal of Animal and Plant Sciences, 2017)
A total of 123 bean genotypes collected from different regions of Turkey and 7 foreign anthracnose-resistant varieties were evaluated for resistance to anthracnose disease caused by the fungal pathogen Colletotrichum lindemuthianum (Sacc. and Magn.) Lambs. Scrib. Analysis was conducted using artificial inoculation as well as resistance-linked molecular markers. Artificial inoculation was performed in a growth chamber using Race 55. Molecular markers were obtained from SCAR [SAS13 (950 bp, Co-42), SC08 (910 bp, Co-4), SF10 (1072 bp, Co-10), SZ04 (567 bp, Co-6)] and RAPD (OA181500 (1500 bp, Co-15) primers associated with resistant genes. Results of artificial inoculation showed that in addition to the 7 foreign varieties, 21 Turkish bean genotypes were anthracnose-resistant, while the remaining 102 Turkish genotypes were not. Moreover, results of molecular-marker screening indicated the presence of one or more amplicons associated with resistant-gene markers (Co-42, Co-4, Co-6, Co-10 and Co-15) in the majority of resistant genotypes. Only one accession (G89) had all 5 amplicons, and 6 accessions (G19, G20, G34, G93, G97 and Jaguar) had no amplicons. The present study discovered Turkish bean germplasm of both Andean and Mesoamerican source to have a high level of resistance against anthracnose Race 55. In addition, amplicons connected with several resistance genes were found in this broad bean germplasm. Bean genotypes distinguished in the present study as anthracnose resistant could be utilized in future reproducing programs.
Keywords: Anthracnose (Colletotrichum lindemuthianum); artificial inoculation; common bean (Phaseolus vulgaris L.); disease resistance; RAPD; SCAR